Performance Evaluation of Employees and Leaders Using the Analytical Hierarchy Process - Luthfi Daffa Hadi Pratama; Renny Rochani (JURNAL ILMIAH RESEARCH STUDENT, 2026)
Purpose – This study aims to develop a structured and objective performance evaluation system for employees and leaders in a company using the Analytical Hierarchy Process (AHP) method. Design/methodology/approach – This research employs a quantitative approach. Data were collected through pairwise comparison questionnaires using the Saaty (1990) scale, which were developed based on the Analytical Hierarchy Process (AHP) method. Respondents were selected using purposive sampling. The collected data were then analyzed to determine the priority weights of each criterion and to assess the consistency of respondents’ judgments. The study was conducted at Cahaya Prima 83 company in Indonesia. Findings – The results show that AHP effectively determines the priority weights of performance evaluation criteria. For employees, the key criteria include attendance, attitude, discipline, and responsibility. For leaders, the criteria include leadership, decision-making, fairness, and responsibility. The method produces a structured ranking system that enhances objectivity and transparency in performance evaluation. Practical implications – The implementation of AHP provides companies with a systematic and reliable decision-making tool for evaluating employees and leaders, which can improve motivation, productivity, and overall organizational performance. Originality/value – This study contributes to the performance management literature by integrating employee and leader evaluation simultaneously using AHP within a company context, which remains relatively underexplored..